Spectroscopic studies of on-surface synthesis of chiral graphene nanoribbons - Chunin, Igor (Trinity College Dublin. School of Physics. Discipline of Physics, 2023)
The field of on-surface synthesis bridges physics, chemistry, material and surface science by combining the tunability of molecular materials, the advantages of self-assembly with the sturdiness of covalently bonded structures which exhibit new electronic structure, behaviour and have fantastic potential that has yet to be fully realised. On-surface synthesis has notably led to atomically precise graphene nanoribbons (GNRs), exhibiting an ever more diverse range of structures and novel properties. Key among these is both their bandgap, which has motivated different edge structures of GNRs, and the electronic mobility, leading to the desire to integrate GNRs into electronic devices such as field effect transistors (FETs). This thesis work focuses on spectroscopic and microscopic studies of a particular type of chiral GNRs grown in-situ on gold and silver crystal surfaces and, after growth, their ex-situ transfer to insulating surfaces, the last is a necessary step in incorporating them in field-effect transistors (FETs) or potentially functionalizing them with molecules for use as sensors. Synchrotron radiation-based X-ray photoemission spectroscopy (XPS), near-edge x-ray absorption fine structure spectroscopy (NEXAFS) and scanning tunnelling microscopy (STM) techniques were employed to study the steps in the on-surface synthesis of GNRs from precursor molecules to their final form. These techniques provided detailed elementally selective spectroscopic information on these molecular-derived systems, orientations and interactions of the precursor molecules with each other and with the surface, and also provide insight into the intramolecular changes during the transformation process from molecules to functional structures such as the intermediate polymerised chains and the final GNR structures. This thesis investigates specific novel chiral graphene nanoribbons which have a stepped zigzag edge (4,1) structure of incorporating oxygen-boron-oxygen along the zigzag edge which enhances their chemical stability while providing additional spectroscopic insights. Synchrotron-based core level spectroscopic in-situ measurements of their on-surface synthesis were studied at the BESSY II (Germany) and MAX- IV (Sweden) synchrotron sources in this work. The observed experimental results are accompanied by relevant core-level spectroscopic electronic structure calculations via density functional theory (DFT) simulations of the observed spectra expected from each stage of the synthesis. The experimental data is interpreted with the aid of the calculated spectra which together confirm that this combination of simulated and measured core level spectroscopies to on-surface synthesis is a useful approach. This experimental approach is then extended to spectroscopically investigate the ex-situ but in-place transfer of these GNRs onto device relevant silicon dioxide surfaces.
APPROVED
Keywords: Chiral nanoribbons; On-surface synthesis; Graphene nanoribbons; Surface science; Near-edge absorption fine structure spectroscopy (NEXAFS); Synchrotron; X-ray photoemission spectroscopy (XPS); Density functional theory (DFT); Scanning tunneling microscopy (STM); OBO